The Study Health and Economic Determinants Shape Human Development Index: Determinan Kesehatan dan Ekonomi Membentuk Indeks Pembangunan Manusia - Nugroho, Wahyu Adi; Saptutyningsih, Endah; Ma’ruf , Ahmad (Academia Open, 2026)
General Background Human development represents a multidimensional paradigm integrating health, education, and living standards as core indicators of societal progress. Specific Background This study examines variations in the Human Development Index (HDI) using panel data across multiple administrative units over the 2019–2023 period, focusing on stunting prevalence, under-five mortality, health facility availability, and regional economic output. Knowledge Gap Prior studies largely emphasize macroeconomic or fiscal variables, with limited integration of chronic health indicators and primary healthcare infrastructure within a unified panel framework. Aims This research aims to identify key determinants shaping HDI through a comprehensive panel regression approach. Results The findings reveal that under-five mortality and the number of inpatient health centers exhibit significant negative relationships with HDI, while regional economic output shows a positive and significant association. Stunting does not demonstrate statistical significance within the observed period. Novelty The study introduces an integrated model combining chronic health indicators and economic variables, highlighting disparities between infrastructure quantity and service quality in shaping development outcomes. Implications The results indicate that improving human development requires reducing child mortality, strengthening the quality and distribution of primary healthcare services, and sustaining inclusive economic growth strategies. Highlights• Under-five mortality consistently reduces human development outcomes• Economic output expansion aligns with higher composite welfare indicators• Health facility expansion without quality alignment yields adverse patterns KeywordsHuman; Development; Mortality; Stunting; Economy